A VLSI median-select voter for fault tolerant signal processing applications - Kin, Keong Wong; Tan, Eng Chong; Abdul Rahman, Abdul Wahab (1996)
A hardware voter'thai serecis ihe has been designed and impleiiienied using ihe latest n-MOS iechiiology Ertensive circuii sirniilafron using MOSSIM and SPICE have been successjiliy carried orii to veri3 the logic and rime response of the chip designed The IC will be usejui for specijc signal processing applications.